Queer Eye: The Moorish Talisman of W.Somerset Maugham - Cody, Mary Kilcline (SARE: Southeast Asian Review of English, 2017)
In his profile and prosperous 67-year career, W. Somerset Maugham wrote "twenty novels, filled nine volumes with his short stories, wrote thirty-one plays, and published seven volumes of prose non-fiction." (Rogal vi). As well as the massive edifice of his literary output, Maugham’s creative, financial and social success was given concrete form in his magnificent villa overlooking the Mediterranean at Cap Ferrat, on the French Riviera.